ANALISIS SIKAP IBU RUMAH TANGGA PRA SEJAHTERA TERHADAP PENGGUNAAN LPG 3 KILOGRAM DI KABUPATEN GOWA PROPINSI SULAWESI SELATAN - Abdullah Abdullah; Andi Ririn Oktaviani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aims to determine the characteristics and attitudes of underprivileged housewives to use LPG 3 kilograms in Gowa in South Sulawesi. Data collection methods are the method of observation , interviews (questionnaire) and a collection of documents related to this study. The type of data in the form of primary data and secondary data. The population is prosperous pre housewife Gowa in South Sulawesi Province kabupeten by taking a sample of 100 people who were selected based on the method of incidental , methods of data analysis in this study is a descriptive analysis , namely to calculate the frequency of respondents by age group, income group, occupational groups, education groups and respondents' attitudes toward various attributes attached to LPG 3 Kg. Respondents attitudes were measured using Multiatribut Fishbein formulation with the aim to help quantify the ordinal be quantitative . The results showed that the characteristics of the pre sejahatera housewife in Gowa regency of South Sulawesi, showed the average age of respondents was 50 years, while 72 percent of respondents were education less than junior high, while the head of the family or the husband's work shows a relatively uniform rate of type respondents work identified in this study , namely farming , laborers , drivers etc. . Family income shows that 86 per cent less than Rp . 1.000.000, - with an average of Rp. 762 000,- is smaller than the local minimum wage (UMR) in 2013 amounted to Rp.1,440,000,- so it does not meet the Living Needs (KHL) . While the average number of dependents per household (HH) ebanyak 4 people . Housewife attitude towards the use of LPG underprivileged 3 Kilograms showed a positive attitude , a positive attitude is interpreted also taste like housewives underprivileged to attribute LPG 3 kilograms, but it also shows that positive attitude affordability housewife underprivileged against LPG price 3 kg. Attributes that most contribute to the positive attitude of underprivileged housewives are the attributes